2006
DOI: 10.1111/j.1464-5491.2006.01865.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing ongoing quality assurance in a retinal screening programme

Abstract: A robust and cost-effective system has been developed to allow monitoring of performance of routine retinal screening which may be extended to meet current national recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The present study observed no progression of retinopathy requiring intervention at any time after the pregnancy in a population of women with considerable greater duration of diabetes. It is unlikely that cases were missed, as the Newcastle screening method has high sensitivity (88%) and specificity (98%), as previously described [21], and because missed cases would be picked up in subsequent years within this single centre study.…”
Section: Discussionsupporting
confidence: 61%
“…The present study observed no progression of retinopathy requiring intervention at any time after the pregnancy in a population of women with considerable greater duration of diabetes. It is unlikely that cases were missed, as the Newcastle screening method has high sensitivity (88%) and specificity (98%), as previously described [21], and because missed cases would be picked up in subsequent years within this single centre study.…”
Section: Discussionsupporting
confidence: 61%
“…2,11 This was satisfactory in the era of Polaroid films. However, by the year 2000, it was possible to use digital images.…”
Section: Quality Assurancementioning
confidence: 96%
“…Our ongoing sensitivity and specificity for detection of sight threatening diabetic retinopathy are currently 93.5% and 97.8%). 11 There is no reason not to incorporate QA into routine screening, but the QA system must be simple and cost effective.…”
Section: State Of the Art Lecturementioning
confidence: 99%
“…For example, a U.K. diabetes center re-graded a percentage of images to determine appropriateness of referrals for clinic examination. 156 Other programs have reported outcomes measuring image quality, intragrader reliability, and percentage of grader-generated reports within 48 h of grading images. 157 …”
Section: Appendix 5: Privileging and Credentialingmentioning
confidence: 99%